Application of microbiological assay to determine pharmaceutical equivalence of generic intravenous antibiotics (2009)
ABSTRACT: Background Demonstration of equivalent amounts of the same active pharmaceutical ingredient (API) between generic and innovator products (pharmaceutical equivalence) is a basic requirement of regulatory agencies for intravenous generic drugs prior to clinical use, and constitutes the pivotal point to assume therapeutic equivalence. Physicochemical methods are preferred instead of biological assays to determine concentration of drugs in biological fluids, but it does not permit direct quantification of potency. Here, we report a microbiological assay using large plates designed to determine potency and concentration of pharmaceutical-grade antibiotics for injection and a statistical method to assess the in vitro equivalence of generic products with respect to the innovator. Methods The assay is based on the concentration-dependent variation of the inhibitory effect of antibiotics on reference bacteria (B. subtilis ATCC 6633, S. aureus ATCC 6538p and S. epidermidis ATCC 12228) in a seeded agar (Difco™ Antibiotic Media), producing a concentration-response linear relationship with two parameters: y-intercept (concentration) and slope (potency). We compared the parameters of 22 generic products (amikacin 4, gentamicin 15, and vancomycin 3 products) against the innovator and the reference powder by Overall Test for Coincidence of the Regression Lines (Graphpad Prism 5.0). Results The validation method yielded excellent results for linearity (r2 ≥ 0.98), precision (intra-assay variation ≤ 11%; inter-assay variation ≤ 10%), accuracy, and specificity tests according to international pharmacopoeial requirements. Except for one generic of vancomycin that had 25% more API (P y-intercept = 0.001), the pharmaceutical equivalence was demonstrated in 21 generics with undistinguishable slopes and intercepts (P > 0.66). Potency estimates were 99.8 to 100.5, 99.7 to 100.2 and 98.5 to 99.9% for generic products of amikacin, gentamicin and vancomycin, respectively. Conclusion The proposed method allows rapid, cost-saving, precise, and accurate determination of pharmaceutical equivalence of drugs in pharmaceutical dosage-form, and may be used as a technique for testing generic antibiotics prior to their approval for human use.